2021
DOI: 10.1097/phh.0000000000001346
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Local Health Departments in Obesity Prevention: A Scoping Review

Abstract: Introduction: Local health department (LHD) obesity prevention (OP) efforts, particularly by rural LHDs, are seemingly uncommon, in part, due to limited infrastructure, workforce capacity, accessible data, and available population-level interventions aimed at social determinants of health (SDOH). Methods: We conducted a scoping review to determine LHD roles in OP efforts and interventions. Inclusion criteria were articles including evidence-based OP and LHD leaders or staff. Articles were coded by type of LHD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…16 Another review observed that smaller and/or rural governmental entities have fewer strategies to combat health disparities than larger and/or urban governmental entities. 17 Looking more specifically at governmental entities' involvement in health equity interventions, one review found that LHD involvement is difficult to ascertain, 18 while others found that community-based interventions in governmental entities were associated with decreasing health disparities. 16,17 This scoping review builds on previous reviews by examining interventions that involve governmental entities that focus on racial/ethnic health equity across the United States.…”
Section: Health Equity Activities In Public Health Agenciesmentioning
confidence: 99%
“…16 Another review observed that smaller and/or rural governmental entities have fewer strategies to combat health disparities than larger and/or urban governmental entities. 17 Looking more specifically at governmental entities' involvement in health equity interventions, one review found that LHD involvement is difficult to ascertain, 18 while others found that community-based interventions in governmental entities were associated with decreasing health disparities. 16,17 This scoping review builds on previous reviews by examining interventions that involve governmental entities that focus on racial/ethnic health equity across the United States.…”
Section: Health Equity Activities In Public Health Agenciesmentioning
confidence: 99%
“…Obesity refers to the disorder of energy balance caused by long-term energy intake exceeding consumption, resulting in the storage of body energy in the form of fat, and the accumulation of fat will damage health [1]. With the development of social economy, obesity has become a common disease, and the number of obese people is gradually increasing, which will lead to some social and economic side effects [2][3][4][5]. Obesity is increasingly concerned.…”
Section: Introductionmentioning
confidence: 99%